A paradox: Increased psicho-social problems-less counselling intervention - Quiles, Cristina Haydée (2005)
This work is based upon conclusions drawn from the research project: "A Profile of vocational occupational counselling and placement and employment services" in La Plata and greater La Plata (Province of Buenos Aires, Argentina). This research was carried out between 1998 and 2002 and explored four axes or systems: Health - Labour-Social Policies and Education. In the case of this last axis, reference was made to information about school counselling teams (psychologists, psycho-pedagogues, social workers, etc.) who should have the responsibility for the counselling task, and moved their activity towards the attention of urgencies requested by educational institutions, to cope with current psycho-social problems, losing sight of the importance of counselling from a prevention perspective, for avoiding possible risk situations. Results achieved within this context (La Plata, capital of the Province of Buenos Aires, Ensenada and Berisso), due to the strategic importance of the region in the national context, allowed us to establish meaningful relationships, correlations and projective inferences in other social and regional spheres.